Implementasi Kebijakan Pelayanan Terpadu Satu Pintu (PTSP) di Pengadilan Agama Kelas I A Kota Depok - Rahmawati Rahmawati; Qiqi Asmara (Jurnal Media Administrasi, 2024)
To improve service quality, the Supreme Court of the Republic of Indonesia issued a Decree of the Director General of the Religious Courts Number 1403.b/DJA/SK/OT.01.3/8/2018 Concerning Guidelines for One-Stop Services in the Religious Courts Environment. With this policy, the Depok Religious Court implemented the One-Stop Integrated Service. In implementing the One Stop Integrated Service at the Depok Religious Court, several obstacles were found in its implementation. The aim of this study is to identify and analyze the implementation of the One Stop Service policy at the Depok Religious Court. The theory of this research uses the theory of policy implementation in the George Edward III model. By using a descriptive method with a qualitative approach. Retrieval of data using interviews, observation and documentation. Meanwhile, to test the validity of the data using triangulation techniques. The results of the research from 4 indicators that regarding communication it is necessary to carry out more socialization because many people do not know about the mechanism in the procedure for handling service cases that exist at PTSP. Resources, in terms of quantity the number of officers at PTSP is still small while the number of cases at the Depok Religious Court is quite a lot. In terms of quality, there is a need for training because there are still officers who are less responsive, and the existing facilities and infrastructure at PTSP have not been integrated all in one door due to limited land. Disposition, the executors have a commitment to carry out this policy by delivering tasks that are good enough in accordance with the contents of the instructions in the policy. Bureaucratic Structure, the officers have carried out the policy in accordance with the applicable SOP. Suggestions from this study are that socialization must be increased and there is a need for land expansion to support infrastructure facilities and additional staff on duty at PTSP so as to maximize service time.